Doctor doctor, please, oh, the mess I’m in : la figure paternelle et le père figurant en tant que signe identificateur du fils nazi dans Les Bienveillantes de Jonathan Littell - Łachacz, Magdalena (Romanica Silesiana)
The article proposes a critical reading of the father figure in Jonathan Littell’s The Kindly Ones. While taking into account various interpretative contributions to the analysis of the theme, formerly neglected and subjected to Julia Kristeva’s theory of abject mother, this article explores an alternative, esthetic, culturally oriented approach to the phenomenon. By grouping together father and a man who, in the absence of the former, takes power over the son, the story’s protagonist, the figure of the father can be understood as a key-symbol of a Nazi perpetrator’s identity. However, the article aims to show that this image can stem from the specific cultural context of contemporary representations of Nazism and influence today’s perception of the perpetrators.